Relationship between percentages of heart rate reserve and oxygen uptake reserve during cycling and running: A validation study - Guimarães, G. C.; Farinatti, P. T. V.; Midgley, A. W.; Vasconcellos, F.; Vigário, P.; Cunha, F. A. (The Journal of Strength and Conditioning Research, 2019)
This study investigated the relationship between percentages of heart rate reserve (%HRR) and oxygen uptake reserve (%VO2R) during a cardiopulmonary exercise test (CPET) and discrete bouts of isocaloric cycling and treadmill running. Thirty men visited the laboratory 3 times for anthropometrical and resting VO2 assessments, and perform cycling and running CPETs. Ten men visited the laboratory twice more to investigate the validity of the %HRR-%VO2R relationships during isocaloric bouts of cycling and running at 75% VO2R with energy expenditures of 400 kcals. The %HRR was significantly higher than the %VO2R during both CPETs at all exercise intensities (p < 0.001). During isocaloric exercise bouts, mean %HRR-%VO2R differences of 6.5% and 7.0% were observed for cycling and running, respectively (p = 0.007-p < 0.001). The %HRR and %VO2R increased over time (p < 0.001), the rate of which was influenced by exercise modality (p < 0.001). On average, heart rate was 5 (p = 0.007) and 8 (p < 0.001) b/min higher than predicted from the second energy expenditure quartile for cycling and running, respectively; however, observed VO2 was lower than predicted during all quartiles for cycling, and the first quartile for running. Consequently, time to achieve the target energy expenditure was greater than predicted (p < 0.01). In conclusion, the %HRR-%VO2R relationship observed during CPET data did not accurately transpose to prolonged isocaloric bouts of cycling and running. In addition, power outputs and speeds defined by the American College of Sports Medicine equations for cycling and running, respectively, overestimated VO2 and energy expenditure.